Frailty and reduced gait speed are independently related to mortality of cirrhotic patients in long-term follow-up - Rubén Soto (Elsevier, 2021)
Introduction and objectives: Frailty is characterized by a poor restoration of homeostasis after a stressor event. Although it is not usually diagnosed, it has been associated with decreased survival in cirrhotic patients. We aimed to evaluate the impact of frailty and decreased gait speed over survival in cirrhotic patients at long-term follow-up. Materials and methods: We included stable cirrhotic patients Child–Pugh B-C or MELD ≥12, ≥50 years old. We performed a clinical evaluation, anthropometry, and laboratory tests. Frailty was diagnosed using Fried Frailty Index. We evaluated survival at a 4-year follow-up. Results: We included 126 patients; mean age 64 ± 8.3 years, median MELD-Na 15[12–17], median follow-up was 881 [349–1277] days. The main etiology was MAFLD (31.4%). Frailty was diagnosed in 65.1% of patients. There were no significant differences in baseline characteristics per frailty condition. Mortality was higher in frail patients than non-frail patients (68.2% versus 20.6% at 48 months, respectively; p-value <0.001). The mean gait speed in frail and non-frail patients was 0.86 ± 0.3 m/s and 1.16 ± 0.2 m/s, respectively (p-value <0.001). Interestingly, 26.9% of patients presented a reduced gait speed (≤0.8 m/s). Patients with decreased gait speed also had higher mortality than patients with normal gait speed (79.9% versus 40.8%, respectively; p-value <0.001). A multivariate-adjusted model showed that decreased gait speed (HR = 3.27, 95%CI:1.74–6.14; p < 0.001) and frailty (HR = 4.24, 95%CI:1.89–9.51; p < 0.001) were associated with mortality. Conclusions: Frailty is independently associated with decreased survival at long-term follow-up. Reduced gait speed is strongly associated with mortality and could be a surrogate marker of frailty in clinical practice.